Akibat Hukum Peralihan Hak Atas Tanah Waris Yang Tidak Didaftarkan Di Kantor Pertanahan Kabupaten Sleman - Irfan Aditya Semana (Officium Notarium, 2022)
This study aims to identify and describe the transfer of land rights due to inheritance that is not registered. To analyse and describe the reasons for heirs with inheritance rights but opted not to register their rights in accordance with Government Regulation Number 24 of 1997. The research method uses qualitative with empirical characteristics. The subjects in this study were people who received inheritance and chose not to register, the registration of the transfer of rights officer, Mr. Carik in Margomulyo Village, Head of Sleman BPN land registration The approach method used in this study is a sociological juridical approach. Retrieval of data using the Interview method. Technical data analysis using qualitative juridical analysis. The results of the study concluded that the legal consequences if the transfer of land rights is due to inheritance that is not registered according to Government Regulation Number 24 of 1997, namely the heirs as the holders of inherited land rights will not be guaranteed legal certainty because of the absence of proof of certificate of land ownership considering a certificate serves as a written proof of rights on behalf of the heirs, and due to the failure to register their land to the Sleman Regency BPN, the heirs are unable carry out legal actions such as sale and purchase, grants, exchanges, distribution of joint rights and entry into the company. The reason for the heirs who received inheritance rights but chose not to register their rights in accordance with Government Regulation Number 24 of 1997, are due to the land registration process which according to residents, has been complicated and required a lenghty process. Lack of knowledge from residents also prevents them from immediate registeration hence conflicts arise over inheritance between families. The other reason is that the community tends not register their land by considering the members of their family or relatives who have not agreed on the distribution of the land, thus the process of registering inherited land cannot be carried out as it requires the signature of the relatives to the heirKey Word: Transfer of Rights, Inheritance, Non registeration AbstrakPenelitian ini bertujuan mengetahui dan menjelaskan peralihan hak atas tanah karena pewarisan yang tidak didaftarkan. Mengetahui dan menjelaskan alasan ahli waris yang mendapatkan hak waris tidak mendaftarkan haknya sesuai dengan Peraturan Pemerintah Nomor 24 Tahun 1997. Metode penelitian menggunakan kualitatif dengan sifat empiris. Subjek dalam penelitian ini yaitu orang yang menerima waris dan tidak mendaftarkan, seksi pencatatan peralihan hak, pak carik di Kelurahan Margomulyo, Kasi pendaftaran tanah BPN Sleman. Metode pendekatan yang digunakan dalam penelitian ini adalah pendekatan yuridis sosiologis. Pengambilan data menggunakan metode Interview. Teknis analisis data menggunakan analisis yuridis kualitatif. Hasil penelitian menyimpulkan bahwa akibat hukumnya apabila peralihan hak atas tanah karena pewarisan yang tidak didaftarkan menurut Peraturan Pemerintah Nomor 24 Tahun 1997 yaitu ahli waris sebagai pemegang hak atas tanah pewarisan tidak akan mendapat jaminan kepastian hukum karena ahli waris tidak mempunyai bukti sertipikat kepemilikan tanah sebagai surat tanda bukti hak yang tertulis atas nama ahli waris karena ahli waris tidak mendaftarkan tanahnya ke BPN Kabupaten Sleman sehingga ahli waris tidak dapat melakukan perbuatan hukum seperti Jual Beli, Hibah, Tukar Menukar, Pembagian Hak Bersama dan Pemasukan dalam perusahaan. Alasan ahli waris yang mendapatkan hak waris tidak mendaftarkan haknya sesuai dengan Peraturan Pemerintah Nomor 24 Tahun 1997 yaitu Ahli Waris Tidak Mendaftarkan Tanah Warisnya karena proses pendaftaran tanah yang menurut warga berbelit-belit dan membutuhkan proses lama. Kurangnya pengetahuan dari warga sehingga tidak langsung mendaftarkan sehingga terkadang muncul konflik perebutan tanah waris antar keluarga. Alasan selanjutnya yaitu masyarakat tidak mendaftarkan tanahnya karena masih ada keluarga yang belum sepakat atas pembagian tanah, sehingga proses pendaftaran tanah waris tidak dapat dilakukan karena salah satu persyaratanya yaitu tanda tangan keluarga waris.Kata-kata Kunci: Peralihan Hak, Pewarisan,Tidak didaftarkan